A cause of water-sensitivity in modern oil paint films: The formation of magnesium sulphate. (January 2014) - Silvester, Genevieve; Burnstock, Aviva; Megens, Luc; Learner, Tom; Chiari, Giacomo; van den Berg, Klaas Jan
Abstract : Unvarnished twentieth-century oil paintings are often sensitive to aqueous swabbing, a method routinely employed by conservators for surface cleaning. This study proposes a connection between sensitivity and the presence of magnesium sulphate heptahydrate which has been identified on the surface of some of water-sensitive paintings. The probable source of magnesium is magnesium carbonate, an additive in some twentieth-century oil paints, which has reacted with atmospheric sulphur dioxide (SO2 ). Films made using modern manufactured paints and formulations made in the laboratory were exposed to gaseous SO2 and raised relative humidity and examined using scanning electron microscopy with energy dispersive X-ray spectroscopy and X-ray diffraction to characterize the crystalline entities. Films containing magnesium carbonate formed magnesium sulphite and sulphate hydrates. Films containing zinc oxide were also investigated. These formed zinc and sulphur containing salts. Sensitivity to swabbing with water before and after exposure was evaluated. Films that developed salts, demonstrated increased sensitivity to aqueous swabbing after exposure to SO2 . Findings suggest that increased water sensitivity may be due to a combination of the formation of hygroscopic degradation products and to weakening of the paint film due to salt-induced disruption of the surface.